Risk and protective factors associated with substance use among Puerto Rican youths after Hurricane María: a cross-sectional study - Juan Carlos Gonzalez; Daniel K. Feinberg; Regan W. Stewart; John Young; Rosaura Orengo-Aguayo (BMC, 2024)
Abstract Background Identifying factors associated with post-disaster youth substance use is a crucial element of developing evidence-based prevention and intervention efforts. Hurricane María struck Puerto Rico in September of 2017 and the wide-spread impact from this disaster, including exposure to trauma, displacement, and disrupted social supports had the potential to negatively impact levels of substance use among youth across the archipelago. However, post-disaster substance use remains under-investigated in this context. The current study sought to identify risk and protective factors associated with substance use among Puerto Rican youth in the aftermath of Hurricane Maria. Methods Cross-sectional, secondary data analyses were conducted using school-based survey data collected at all schools in Puerto Rico between February 1 and June 29, 2018 (5-9 months after Hurricane María). Social supports, substance use, and trauma symptoms were assessed. An ordinal regression analysis was conducted to identify student factors associated with greater likelihood of post-disaster substance use. Results A total of 36,485 participants (50.7% female, grades 7-12), were included in an ordinal regression analysis that compared the likelihood of respondents endorsing high, low, or no substance use after Hurricane María based on reported adult social support, counselor/teacher social support, peer social support, ptsd symptomatology, and gender. Findings showed that, when compared to students that endorsed low or no substance use, those who reported having adult social support demonstrated a 58% reduction in odds (OR = 0.42, 95% CI: 0.34-0.53) of reporting high substance use after Hurricane María, while students who reported having teacher/counselor social support demonstrated a 21% reduction in odds (OR = 0.79, 95% CI: 0.69-0.89) of reporting high substance use. Additionally, those that reported having peer social support demonstrated a 31% increase in odds (OR = 1.31, 95% CI: 1.10 to 1.58) of reporting higher substance use, compared to those that reported low or no substance use. Conclusions While social support was generally protective, prevention efforts to build positive family and community connections may be indicated. Evidence-based school screenings of substance use and trauma may help direct intervention to those most at risk for co-occurring issues.